Hubungan Masa Kerja dengan Kandungan Karboksihemoglobin (COHb) dalam Darah Polisi Lalulintas di Jalan Slamet Riyadi Surakarta - Ahirawati, ; Astuti, Dwi (Jurnal Kedokteran Indonesia, 2009)
Background: This study aimed to determine the correlation between duration of work and blood COHb level among traffic policemen at Slamet Riyadi Street Surakarta.Methods: It was a cross sectional study with a sample of 32 the policemen on duty at the police stations at Slamet Riyadi Street. The sample was selected by purposive sampling.Results: The result showed that 1 â 5 years duration of work tended to increase blood COHb from 1.5to 4.6 ppm. Duration of work was strongly correlated with blood COHb (r = 0.8; p < 0.001).Conclusion: Duration of work is strongly correlated with blood COHb level among traffic policemen,and is statistically significant. Jurnal Kedokteran Indonesia: 1 (1):76-82Keywords: CO, COHb, traffic police